Modifying a Rubber Ball (Pentul) as an Auxiliary Media for Children's Learning Motivation in Playing Basketball in Corner Learning in Class VI of SD Negeri 79 South Bengkulu for the 2020/2021 Academic Year - Saputra, Oven Julian; Supriyanto, Supriyanto; Ferdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This study aims to foster children's learning motivation in playing basketball through the use of a rubber ball in grade VI children of SD Negeri 79 South Bengkulu, South Bengkulu Regency for the 2020/2021 academic year. The method in this study used class action research methods. The sample in the study totaled 12 people, namely 7 girls and 5 men. Based on the results of the study it can be described that the implementation of learning basketball games through the use of rubber balls (pins), in SD Negeri 79 Bengkulu Selatan, South Bengkulu Regency, the activities of researchers in teaching basketball games through the use of rubber balls (pins) in the first cycle were 75% complete while the remaining 25% has not been completed. In the second cycle, after making improvements to the lesson plans, the research activities in teaching reached 83.3% of the students, while 16.7% were not finished. In this second cycle there was an increase of 8.3%. Referring to indicators of achievement of research activities in teaching and student activities in participating in learning by 80%, and the results of the second cycle are said to be successful and have very good qualifications (A). Student activity in participating in learning basketball games through the use of rubber balls (pentul) reached 80% and the remaining 20% ​​had not participated in basketball learning using rubber balls, whereas in the second cycle after changing the learning scenario in lesson plans, student activities in participating in learning reached 83.3%, this means that there is an increase of 8.3% in the implementation of the second cycle.